Deciphering heat wave effects on wheat grain: focusing on the starch fraction - Pereira, Rita; Tomás, Diana; Silva, Manuela (Frontiers in Plant Science, 2024)
Wheat is an essential staple food, and its production and grain quality are affected by extreme temperature events. These effects are even more relevant considering the increasing food demand for a growing world population and the predicted augmented frequency of heat waves. This study investigated the impact of simulated heat wave (HW) conditions imposed during grain filling on starch granule characteristics, endosperm ultrastructure, and transcriptomic modulation of genes involved in starch synthesis and degradation. All these evaluations were performed with four different genotypes, two commercial wheat varieties (Antequera and Bancal) and two traditional landraces (Ardito and Magueija). Starch granule size distribution and shape were significantly altered by HW treatment, revealing an increase of A-type granules in Ardito and an opposite effect in Magueija and Bancal, while Antequera remained stable. Analysis of the largest (LD) and smallest (SD) granule diameters also revealed genotype-specific changes, with Magueija showing a shift towards more spherical A-type granules after HW treatment. Scanning electron microscopy confirmed alterations in endosperm morphology, including increased vitreousness in Bancal and substantial increase of endosperm cavities and grain size reduction in Magueija under HW stress. Transcriptomic analysis confirmed the stability of Antequera under HW, in contrast with the other genotypes were differential gene expression related to starch metabolism was detected. These effects were particularly severe in Magueija with the downregulation of genes encoding for enzymes involved in amylopectine synthesis (both starch synthases and starch branching enzyme) and upregulation of α-amylase encoding genes. These findings contribute to the understanding of heat stress effects on wheat grain quality, emphasize the importance of genetic diversity in HW responses, and suggest potential avenues for breeding climate-resilient wheat varieties.